STRATEGI BATNA (BEST ALTERNATIVE TO A NEGOTIATED AGREEMENT) DALAM MENGATASI KONFLIK MANAJEMEN LINGKUNGAN DI PERTAMBANGAN - Edwin Umboh (Jurnal Green Growth dan Manajemen Lingkungan, 2017)
The purpose of this research is to know the strategy of BATNA (Best Alternative to a Negotiated Agreement) in overcoming the conflict of environmental management that occurred in mining area of ​​PT. SumberEnergi Jaya, East Motoling District.This study uses descriptive method, which aims to find information from a phenomenon.Strategy management of conflict resolution of mining resources, conducted by PT. SumberEnergi Jaya showed good results, although there are still some residents who have not received the results of negotiations. With the efforts of family approach and deliberation to show effective results, a negotiator's strategy is a critical determinant of the success of an agreement. While Implementation of Law no. 7 of 2012 in this case has not been fully implemented as expected, where from the analysis conducted there is still an omission element by the government. The impact of government policies through the enactment of mining business licenses granted to PT. SumberEnergi Jaya, is very impact on social life and the environment, rather than the economic value generated. Due to the decline in environmental quality will affect the social and economic life of residents around the mine's circle.